2013
DOI: 10.1111/jmp.12039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical restraint on glucose tolerance in cynomolgus monkeys

Abstract: The responses to a glucose challenge are altered by different restraint procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…From another perspective, carbohydrates and saturated fatty acids have been reported to be preferred by people with chronic stress, resulting in weight gain 4 . It has been reported that the concentration of cortisol in Cynomolgus monkey is increased by restraint stress 5 . On the other hand, exercise can enhance resistance to stress and suppressed anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…From another perspective, carbohydrates and saturated fatty acids have been reported to be preferred by people with chronic stress, resulting in weight gain 4 . It has been reported that the concentration of cortisol in Cynomolgus monkey is increased by restraint stress 5 . On the other hand, exercise can enhance resistance to stress and suppressed anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated in two species of macaques that ketamine might invalidate oral carbohydrate tolerance tests by delaying gastric emptying. 32 Given that physical restraint has been shown to affect the response to glucose challenge, 33 these collective findings suggest that definitive evaluation of reproducibility of OGTT response in nonhuman primates may warrant further method development.…”
Section: Discussionmentioning
confidence: 99%
“…Conducting the very best science depends on keeping abreast of the latest knowledge and techniques, not just in research methods and scientific procedures, but also in NHP behaviour, management and welfare, as increasingly studies demonstrate a link between good animal welfare and quality of science (Graham et al, 2011;Guth et al, 2009;Reinhardt, 2004;Schnell and Gerber, 1997;Shirasaki et al, 2013). Researchers, veterinarians and animal care staff should therefore supplement their initial training with continuing learning and professional development, part of which can be provided by resources online.…”
Section: Discussionmentioning
confidence: 99%